Hubungan Antara Stres Peranan dan Ketandusan Upaya - Mohammad Amin, Hassan (2008)
The purpose of this study is to make a research in relation between role stress and burnout among (SABK) teachers in four schools in Perlis. This study is to identify relationship between role stress, role conflict, role ambiguity, role overload, burnout, and demographics variable as wel1. A total of 103 teachers were involved in this study. The questionnaire consist of three section. The probability sampling technique was used in this study The finding indicate that. role stress does not effect the burnout in organization and there is significant relationship between role stress and burnout. Hopefully that the result of this study could bring information and benefits for those who concern to prevent burnout which brought negative impacts to teachers and organizations.